STUDI DE-BOTTLENECKING LAPANGAN MINYAK X UNTUK MENGEVALUASI PENINGKATAN PRODUKTIVITAS MELALUI PENGURANGAN TEKANAN SISTEM DENGAN INSTALASI BOOSTER PUMP - Taufan, Muhammad
X Area is a field owned by one of Oil and Gas Company in Indonesia which is operating as a contractor with Production Sharing Contract deal with the Indonesian Government. Currently X Area has 14 offshore platforms which consist of 63 production wells and one process platform. The entire production wells are using Electric Submersible Pump (ESP). In the course of production process and pressure drop in the bottom hole pressure , dissolved gas in oil will separate into casing annulus which causes increasing casing pressure causing several issues including, bottlenecking phenomenon resulting from the casing pressure exceeds the riser pressure and decreasing fluid level. The problem becomes more complicated when all the wells merged into one integrated system, several wells were decreasing their productivity or even the production were shut down. The objective of this paper is to estimate the optimum operating system pressure and evaluate productivity improvement through system pressure reduction by installing booster pump. The evaluation methods used include modeling and simulation (matching) wells and the results used to develop subsea pipeline network model and simulation using commercial simulator. After getting matching results, optimization scenarios performed including the addition of booster pump. The results of this study showed an increase 50.8% in productivity compared to the actual conditions